Transmembrane serine protease 2 is a prognostic factor for lung adenocarcinoma - Schneider, Marc; Richtmann, Sarah; Gründing, Anna R.; Wrenger, Sabine; Welte, Tobias; Meister, Michael; Kriegsmann, Mark; Winter, Hauke; Muley, Thomas; Janciauskiene, Sabina (International journal of oncology, 2022)
Transmembrane serine protease 2 (TMPRSS2) has been intensively investigated during the current Sars‑CoV‑2 pandemic as a virus activating protease. Furthermore, TMPRSS2 is an oncogenic gene associated with several cancer entities. Co‑expression of TMPRSS2 and serpin family A member 1 (SERPINA1) (encoding alpha‑1‑antitrypsin; AAT) has been reported in the human lung. Recently, AAT was identified as a novel TMPRSS2 inhibitor. We previously reported that lower SERPINA1 expression in tumor tissues and higher levels of plasma AAT are associated with worse survival of patients with non‑small cell lung cancer (NSCLC). In the present study, we sought to examine TMPRSS2 and SERPINA1/AAT expression in tumor and adjacent lung tissues from 347 NSCLC patients. Based on clinical data and gene expression analysis, we performed Cox regression for the survival analysis, and correlated TMPRSS2 and AAT protein levels in tissue samples by immunohistochemical and western blot analyses. We found that lower TMPRSS2 expression in tumor compared to adjacent non‑tumor tissues is linked to a poor overall survival in patients with adenocarcinoma (ADC) and those who are current smokers. IHC staining of TMPRSS2 validated our findings in regard to overall survival while we did not observe a correlation with AAT staining. Based on western blot analyses, we found only a slight negative correlation between full‑length TMPRSS2 and AAT in non‑tumor tissues, which seems to be related to smoking status. Taken together, we demonstrated that TMPRSS2 is a prognostic factor in patients with lung ADC; however, a link between AAT and TMPRSS2 proteins warrants further investigation.
Gesehen am 30.05.2022